Reimagining humanitarianism: relational accountability in locally-led responses - Cindy Horst; Cathrine Brun; Hilde Refstie (Fennia: International Journal of Geography)
In debates on humanitarianism in the last decade or so, ‘localisation’ has been a central concern, broadly referring to the transfer of decision-making power, resources, and responsibility to local and national actors. While the inclusion of certain actors such as local and national non-governmental organisations (NGOs) is relatively straightforward, incorporating others — like affected communities themselves or local less formal civil society — is often more complex. The special issue on reimagining humanitarianism examines the transformative potential of centering communitarian practices, including mutual assistance networks, relational support systems, and local accountability frameworks, in order to rethink humanitarian action from the ground up.